Development of Fertilizer Prescription Targeted Yield-Equation for Carrot Crop Based on Soil Test Values - P K Basavaraja; P N Narasimha Reddy; N L Rajesh; K B Apoorva (Journal of Horticultural Sciences, 2011)
A field experiment was conducted on red soils (Kandic paleustalfs) of Zonal Agricultural Research Station, GKVK, Bangalore during kharif 2008-09 to develop a targeted yield equation for carrot crop. After developing three levels of fertility gradient with respect to available NPK in soil, the main experiment was conducted by taking carrot as a test crop. Initial soil data, carrot root yield and NPK uptake by carrot crop were used for obtaining four important basic parameters, viz., nutrients required to produce a quintal of carrot roots (NR%), contribution of nutrients from fertilizers (CF%), contribution of nutrients from soil (CS%) and contribution of nutrients from organic matter (%C-OM). These parameters were used for developing fertilizer-adjustment targeted yield equation. Comparison of the present soil testing laboratory method with Soil Test Crop Response approach of fertilizer recommendation clearly indicated superiority of STCR targeted yield approach for efficient and economic use of fertilizers to attain the required yield target.